2019
DOI: 10.3389/fmicb.2019.02753
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular DNA: A Nutritional Trigger of Mycoplasma bovis Cytotoxicity

Abstract: Microbial access to host nutrients is a key factor of the host-pathogen interplay. With their nearly minimal genome, wall-less bacteria of the class Mollicutes have limited metabolic capacities and largely depend on host nutrients for their survival. Despite these limitations, host-restricted mycoplasmas are widely distributed in nature and many species are pathogenic for humans and animals. Yet, only partial information is available regarding the mechanisms evolved by these minimal pathogens to meet their nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 83 publications
(106 reference statements)
0
25
0
1
Order By: Relevance
“…The moderate increase in mycoplasma titers observed at 72h in MEM medium alone is likely to be stimulated by the release of nutrients from the inoculum, such as DNA, which was recently identified as a limiting factor for M . bovis proliferation under cell culture conditions [ 32 ]. By using this screening strategy, 39 mutants were identified and further characterized by comparing their proliferation under axenic (PPLO medium) and cell culture conditions ( Fig 1B ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The moderate increase in mycoplasma titers observed at 72h in MEM medium alone is likely to be stimulated by the release of nutrients from the inoculum, such as DNA, which was recently identified as a limiting factor for M . bovis proliferation under cell culture conditions [ 32 ]. By using this screening strategy, 39 mutants were identified and further characterized by comparing their proliferation under axenic (PPLO medium) and cell culture conditions ( Fig 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…These laboratory conditions have largely contributed to the understanding of the biology of these minimal bacteria but provided only limited information on the strategies these organisms have evolved to secure their survival in the animal host and get access to essential nutritional resources. In the absence of small animal models, eukaryotic cell cultures as re-emerged as a valuable environment to revisit the minimal cell concept at the light of host-pathogen interactions [30][31][32][33]44]. Our functional genomic study with the genome-reduced pathogen M. bovis revealed that phosphodiesterases involved in cyclic dinucleotides and nanoRNAs degradation are critical for survival under cell culture conditions, while dispensable in axenic medium.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations